Experimental study of the reflection of light radiation from crystalline particles in the lower troposphere - Galileiskii, Viktor P.; Grishin, A. I.; Elizarov, Alexey I.; Kruchkov, A. V.; Matvienko, Gennadij G.; Morozov, Aleksandr M. (Atmospheric and oceanic optics)
We considered the phenomenon of reflection of light radiation from crystalline particles preferentially oriented in the atmosphere, as well as the physical patterns and possible conditions favoring this reflection. Experimental observations were used to analyze the recorded light spots, occurring due to reflection of radiation from layers of these particles. We describe a case of recording specular layers using a panoramic optical station (AllSky system).